Compact high‐power broadband absorptive filters using slotted waveguide harmonic pads. Issue 9 (1st June 2014) - Stander, Tinus; Meyer, Petrie; Willem van der Walt, Pieter
Abstract : A compact high‐power broadband absorptive filter is designed by cascading a slotted waveguide harmonic pad with a wide stop‐band reflective filter. Absorption is achieved by coupling a surface current standing wave to absorptive external auxiliary waveguides through a cascade of transversal broadwall slots in rectangular waveguide.